A mass spectrometry-based strategy for investigating volatile molecular interactions in microbial consortia: unveiling a Fusarium-specific induction of an antifungal compound - Azzollini, Antonio; Sgorbini, Barbara; Lecoultre, Nicole; Bicchi, Carlo; Wolfender, Jean-Luc; Rubiolo, Patrizia; Gindro, Katia (Frontiers in Microbiology, 2025)
Co-cultivation of microorganisms has emerged as a promising methodology for deciphering the intricate molecular interactions between species. This approach facilitates the replication of natural niches of ecological or clinical relevance where microbes consistently interact. In this context, increasing attention has been addressed toward elucidating the molecular crosstalk within fungal co-cultures. However, a major challenge in this area of research is determining the fungal origin of metabolites induced in co-cultivation systems. Molecules elicited in co-cultures may not be detectable in the individual cultures, making it challenging to establish which microorganism is responsible for their induction. For agar-diffused metabolites, imaging mass spectrometry can help overcome this obstacle by localizing the induced molecules during fungal confrontations. For volatile metabolites, however, this remains an open problem. To address this issue, in this study, a three-head-to-head co-culture strategy was developed, specifically focusing on the exploration of volatile interactions between fungi via headspace solid-phase microextraction combined with gas chromatography mass spectrometry. This methodology was applied to study the volatile molecular interactions of three fungal species: Fusarium culmorum, Aspergillus amstelodami, and Cladosporium cladosporioides. The adopted strategy revealed a Fusarium-specific induction of three volatile molecules: γ-terpinene and two unidentified sesquiterpene compounds. Interestingly, γ-terpinene showed antifungal activity in a bioassay against the other two fungal species: Aspergillus amstelodami and Cladosporium cladosporioides. The proposed methodology could help to investigate volatile molecular interactions and highlight metabolite induction specific to a particular fungus involved in in vitro fungal confrontations. This is relevant for a better understanding of the complex biosynthetic responses of fungi in consortia and for identifying volatile molecules with antifungal activity.